Elimination of Extracellular Adenosine Triphosphate for the Rapid Prediction of Quantitative Plate Counts in 24 h Time-Kill Studies against Carbapenem-Resistant Gram-Negative Bacteria - Yiying Cai; Jonathan J. Ng; Hui Leck; Jocelyn Q. Teo; Jia-Xuan Goh; Winnie Lee; Tse-Hsien Koh; Thuan-Tong Tan; Tze-Peng Lim; Andrea L. Kwa (Microorganisms, 2020)
Traditional in vitro time-kill studies (TKSs) require viable plating, which is tedious and time-consuming. We used ATP bioluminescence, with the removal of extracellular ATP (EC-ATP), as a surrogate for viable plating in TKSs against carbapenem-resistant Gram-negative bacteria (CR-GNB). Twenty-four-hour TKSs were conducted using eight clinical CR-GNB (two Escherichia coli, two Klebsiella spp., two Acinetobacter baumannii, two Pseudomonas aeruginosa) with multiple single and two-antibiotic combinations. ATP bioluminescence and viable counts were determined at each timepoint (0, 2, 4, 8, 24 h), with and without apyrase treatment. Correlation between ATP bioluminescence and viable counts was determined for apyrase-treated and non-apyrase-treated samples. Receiver operator characteristic curves were plotted to determine the optimal luminescence threshold to discriminate between inhibitory/non-inhibitory and bactericidal/non-bactericidal combinations, compared to viable counts. After treatment of bacteria with 2 U/mL apyrase for 15 min at 37 °C, correlation to viable counts was significantly higher compared to untreated samples (p < 0.01). Predictive accuracies of ATP bioluminescence were also significantly higher for apyrase-treated samples in distinguishing inhibitory (p < 0.01) and bactericidal (p = 0.03) combinations against CR-GNB compared to untreated samples, when all species were collectively analyzed. We found that ATP bioluminescence can potentially replace viable plating in TKS. Our assay also has applications in in vitro and in vivo infection models.